Digitalisasi Pelayanan Pensiun Aparatur Negara pada Taspen (Studi Tentang Taspen Ototentikasi di PT Taspen (Persero) KCU Kota Bandar Lampung) - Muhammad Faizal; Dedy Hermawan; Eko Budi Sulistio (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2020)
After the release of the Taspen Authentication application PT. Taspen (Persero) KCU Bandar Lampung system in serving the management of retirement is still not optimal from the stage of entering the pension file to the stage of recording Authentication such as facial recording, voice recording, fingerprint recording still have obstacles in its implementation. The purpose of this study was to determine the pension services carried out by PT. Taspen (Persero) KCU Bandar Lampung City after the digital Taspen Authentication and to find out the obstacles faced by PT Taspen and retired participants in using the Taspen Authentication application digitally. This type of research is a type of qualitative descriptive research. Hasil penelitian menunjukkan jasa pensiun yang dilakukan oleh PT. Taspen (Persero) KCU Kota Bandar Lampung setelah adanya taspenambahan digital belum maksimal, banyak informasi kepada masyarakat sehingga masih banyak yang belum mengetahui tentang penghematan, efisiensi dan responsivitas pembayaran PNS di PT. Taspen (Persero). The obstacles faced by PT Taspen and retired participants in using the Taspen application digitally authentication is the application system is not yet perfect (error system), not all people understand digital technology, the maximum socialization of Taspen authentication.